Fungal isolates and metabolites in locally processed rice from five agro-ecological zones of Nigeria. Issue 4 (1st October 2016) - Abdus-Salaam, Rofiat; Atanda, Olusegun; Fanelli, Francesca; Sulyok, Micheal; Cozzi, Giuseppe; Bavaro, Simona; Krska, Rudolf; Logrieco, Antonio F.; Ezekiel, Chibundu N.; Salami, Waheed A.
ABSTRACT: This study reports the distribution of fungal isolates and fungal metabolites that naturally contaminate locally processed rice from five agro-ecological zones of Nigeria. The fungal species were isolated by the dilution plate technique and identified by appropriate diagnostics, while metabolites were determined by a liquid chromatographic tandem mass spectrometric method. A spergillus and Penicillium species were the predominant isolates found in the rice samples while Fusarium spp. were not isolated. The mean fungal count differed significantly ( p  < 0.05) across the zones and ranged from 9.98 × 10 2  cfu g −1 in the Southern Guinea Savannah to 96.97 × 10 2  cfu g −1 in the Derived Savannah. For 16 fungal metabolites, selected from 63 positively identified fungal metabolites based on their concentration and spread across the zones, an occurrence map was constructed. The Northern Guinea Savannah recorded the highest contamination of fungal metabolites while the Sudan Savannah zone recorded the least.